CONSTRUCT OF MEASUREMENT OF NATIONAL COMMITMENT INDONESIAN INTEGRATED ISLAMIC SCHOOL EDUCATION STAFF - Ridha, Achmad Rasyid; Kasori, K (Proceeding of International Conference of Islamic Education, 2023)
The study of national commitment is something abstract and subjective because it involves the affective domain, both ideological and psychological. It is necessary to create a measurement instrument to minimize the distance between research results and field realities. This study aims to produce valid and reliable instruments for measuring national commitment based on the constructs used in the preparation of dimensions and indicators. The discussion of national commitment in this text divides into (two) dimensions namely the dimension of commitment to the basis of the state; and the dimension of commitment to national sovereignty. The dimension of commitment to the state consists of 5 (five) indicators and the dimension of commitment to national sovereignty consists of 3 (three) indicators. The research subjects totaled 149 (one hundred 149) people. They are educators and educational staff of the Integrated Islamic School who are members of the Indonesian Integrated Islamic School Network (JSIT). This writing went through 3 (three) research stages including the initial stage in the form of literature study, the development stage and the presentation stage. The method used is a quantitative research method through field trials with measurement methods and in analysis using the Smart-PLS 3.3 application through reflective construction by confirmatory factor analysis (CFA). Based on the confirmatory factor analysis of the dimensions and indicators of national commitment, it is valid and reliable. All dimensions measured show results with a factor loading above 0.7. Each dimension and indicator is stated to be able to reflect and form the construct of national commitment. Therefore, the model for measuring national commitment can be accepted according to empirical data obtained from field trials. With a tool for measuring national commitment, it is hoped that prejude will be avoided with political nuances. National commitment must be defined honestly, not based on momentary political interests. It is hoped that this instrument for measuring national commitment can be used by any institution, especially formal education institutions, in assessing the level of national commitment of an employee, teacher or employee.